2017
DOI: 10.1021/acscatal.6b02682
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the Diels–Alder Reaction of Furan and Methyl Acrylate in Lewis Acidic Zeolites

Abstract: Diels−Alder (DA) reactions of furans yield oxanorbornene derivatives which can be converted to a variety of molecules, ranging from molecules of biological interest to naturally occurring organic compounds, and to aromatics via dehydration, a promising alternative for the synthesis of aromatics from renewables. With furan being one of the less reactive dienes, the development of Lewis acidic heterogeneous catalysts, without the shortcomings of the traditional homogeneous catalysts, is critically important. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…In addition, catalysts (such as Lewis acids) can influence the HOMO-LUMO gap by coordinating the HOMO or the LUMO energy of the addends and increasing the interaction between HOMO and LUMO, aiming to improve the reaction rate accordingly. [132][133][134][135] The interaction between HOMO and LUMO is the main factor that determines the ease of reaction and the regioselectivity and stereoselectivity of the DA cycloadducts. 129 Control of HOMO-LUMO interactions may be crucial for obtaining domain isomers of specific structures.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…In addition, catalysts (such as Lewis acids) can influence the HOMO-LUMO gap by coordinating the HOMO or the LUMO energy of the addends and increasing the interaction between HOMO and LUMO, aiming to improve the reaction rate accordingly. [132][133][134][135] The interaction between HOMO and LUMO is the main factor that determines the ease of reaction and the regioselectivity and stereoselectivity of the DA cycloadducts. 129 Control of HOMO-LUMO interactions may be crucial for obtaining domain isomers of specific structures.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…3 It has been found that the DA reaction can be catalysed by Lewis acid sites (LAS) but not Brønsted acid sites (BAS), 3,24 whereas the dehydration of the bicyclic intermediate, which cannot occur in reasonable rates uncatalysed, is facilitated by both LAS and tremendously by BAS. [24][25][26] Overall, the route to p-xylene via DACD is kinetically limited by the cycloaddition over BAS and dehydration on LAS. 22,24,27,28 Industrial production of commodity chemicals demands continuous processes and the manufacturing of BTX compounds is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 For the low-level molecular mechanics (MM) layer, the universal force field (UFF) method was adopted. [55][56][57][58][59] The UFF method can effectively incorporate the extended confinement effects in zeolite catalysis. [60][61][62] The coulombic interaction between the QM and MM layers was considered by employing an electronic embedding scheme.…”
Section: Methodsmentioning
confidence: 99%